2021
DOI: 10.18196/jai.v23i1.12767
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Board Diversity and Sustainability Reporting: Empirical Evidence from Indonesia Before and During COVID-19

Abstract: Research aims: This study aims to investigate how the influence of board diversity before and during the COVID-19 pandemic.Design/Methodology/Approach: The researchers used purposive sampling method. The research sample was 70 companies in the pre-pandemic period and 52 companies during the pandemic with the following criteria: all companies in Indonesia listed on the IDX that published complete sustainability reports and annual reports. In testing the hypotheses, multiple linear regression analysis was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…The results present that the coefficient estimate of DIB is not significantly related to ICD ( p -value = 0.17), which confirms H4. The finding is consistent with the prior study by Juwita and Honggowati (2022) that examined Indonesian-listed firms but found no influence of DIB on sustainability disclosures during the COVID-19 period. Hoang et al (2018) study examined Vietnamese-listed firms with a domestic focus, which are about corporate social disclosure.…”
Section: Resultssupporting
confidence: 91%
“…The results present that the coefficient estimate of DIB is not significantly related to ICD ( p -value = 0.17), which confirms H4. The finding is consistent with the prior study by Juwita and Honggowati (2022) that examined Indonesian-listed firms but found no influence of DIB on sustainability disclosures during the COVID-19 period. Hoang et al (2018) study examined Vietnamese-listed firms with a domestic focus, which are about corporate social disclosure.…”
Section: Resultssupporting
confidence: 91%
“…The factors that influence the citations number in the article include a long publishing period and the use of an interesting variable to study, namely the financial performance variable. On the other hand, there are still articles that do not have citations, such as by (Ardiana, 2022;Breliastiti, 2020;Elafify, 2021;Juwita & Honggowati, 2021;Nilasakti & Falikhatun, 2020;Supriyati & Anggraini, 2021). .…”
Section: Community Analysis a Citation Analysismentioning
confidence: 99%
“…When the pressure is inside companies regarding high quality report, companies will produce high quality reports (Rudyanto & Siregar, 2018) . Sustainability reporting is used by stakeholders to evaluate all forms of corporate responsibility activitites to the society as well as presented separately from the annual report (Juwita & Honggowati, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di sisi lain, sejumlah besar penelitian telah menemukan korelasi antara pelaporan keberlanjutan dan kinerja Perusahaan (Aifuwa, 2020). Kehadiran keberagaman dewan mempengaruhi sustainability reporting pada periode sebelum pandemi, namun pada masa pandemi tidak mempengaruhi sustainability report disclosure (Juwita & Honggowati, 2021). Berdasarkan penjelasan di atas, maka peneliti menarik kesimpulan bahwa sustainability reporting berpengaruh postitif terhadap peningkatan kinerja Perusahaan.…”
Section: Kajian Teoritisunclassified